SOA and WS-BPEL : composing service-oriented solutions with PHP and ActiveBPEL - Vasiliev, Yuli (From technologies to solutions., 2007)
Compose Service-Oriented Architecture Solutions with PHP and Open-Source ActiveBPEL with this book and eBook.